Do fodder import and credit loans lead to climate resiliency in the pastoral social-ecological system of Inner Mongolia? - Li, Y.B; Li, W. J. (Ecology and Society, 2021)
Mainstream policies encourage pastoralists to apply credit loans and input exogenous fodder to alleviate the stress caused by climatic variability and uncertainty. Such external inputs induce new driving forces to the coupled pastoral social-ecological system (SES), but their long-term impacts are not fully understood. Taking Sonid Left Banner of Inner Mongolia as a case study area, we applied an agent-based model and Monte Carlo simulation to evaluate the impacts of fodder import and credit loans on the resilience of pastoral SES in terms of pastoralist household livelihood, livestock production, and rangeland health. The results showed that the strategy of importing fodder only in natural disaster years could make the pastoral SES more resilient to climatic variability, while frequent importing of fodder in climatically normal years would increase the vulnerability of the pastoral SES. Credit loans could enhance the resilience of the pastoral SES in general if fodder is not imported or only imported in disaster years, but could reduce the resilience if fodder is imported frequently. Our findings revealed several differences with previous research on fodder input and credit loan effects, indicating that relevant policies should be holistically evaluated from the perspective of social-ecological systems.